Potential Influences of Gut Microbiota on the Formation of Intracranial Aneurysm. Issue 2 (February 2019) - Shikata, Fumiaki; Shimada, Kenji; Sato, Hiroki; Ikedo, Taichi; Kuwabara, Atsushi; Furukawa, Hajime; Korai, Masaaki; Kotoda, Masakazu; Yokosuka, Kimihiko; Makino, Hiroshi; Ziegler, Emma A.; Kudo, Daisuke; et al.
Abstract : Gut microbiota modulates metabolic and immunoregulatory axes and contributes to the pathophysiology of diseases with inflammatory components, such as atherosclerosis, diabetes mellitus, and ischemic stroke. Inflammation is emerging as a critical player in the pathophysiology of an intracranial aneurysm. Therefore, we hypothesized that the gut microbiota affects aneurysm formation by modulating inflammation. We induced intracranial aneurysms in mice by combining systemic hypertension and a single injection of elastase into the cerebrospinal fluid. Depletion of the gut microbiota was achieved via an oral antibiotic cocktail of vancomycin, metronidazole, ampicillin, and neomycin. Antibiotics were given 3 weeks before aneurysm induction and either continued until the end of the experiment or stopped 1 day before aneurysm induction. We also assessed the effects of the gut microbiota depletion on macrophage infiltration and mRNA levels of inflammatory cytokines. Gut microbiota depletion by antibiotics reduced the incidence when antibiotics were started 3 weeks before aneurysm induction and continued until the end of the experiment (83% versus 6%, P <0.001). Even when antibiotics were stopped 1 day before aneurysm induction, the gut microbiota depletion significantly reduced the incidence of aneurysms (86% versus 28%, P <0.05). Both macrophage infiltration and mRNA levels of inflammatory cytokines were reduced with gut microbiota depletion. These findings suggest that the gut microbiota contributes to the pathophysiology of aneurysms by modulating inflammation. Human studies are needed to determine the exact contribution of the gut microbiota to the pathophysiology of aneurysm formation and disease course in humans. Abstract : Supplemental Digital Content is available in the text.